(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background: Hypertension is a major cardiovascular problem across the globe. Electrolytes like magnesium are linked with the pathophysiology of essential hypertension by various studies. Objective: To evaluate the serum magnesium in patients with essential hypertension compared to healthy control. Methods: A case-control study recruited 45 patients with essential hypertension and 45 matched healthy control. The study was conducted in the Medical Outpatient Clinic in the Medical City Teaching Complex, Baghdad, from July 2016 to November 2016. Serum magnesium measured by Atomic Absorption Spectrophotometers (AAS). Results: Serum magnesium was significantly lower in patients with essential hypertension when compared to healthy control. Female had lowest serum Mg in the patients’ group. Mg was low in obese hypertensive patients. Serum Mg tends to be lower with longer duration of hypertensin ( r value-0.227) but it didn’t reach statistical significance (p value 0.133). Conclusion: Serum magnesium levels were found to be low in hypertensive patients when compared with normotensive persons. Keywords: Hypertension, magnesium Citation: Athab AK, Al-Taee HA, Ali AS. Serum magnesium in a sample of iraqi adults with essential hypertension. Iraqi JMS. 2020; 18(2): 117-122. doi: 10.22578/IJMS.18.2.5